On the Origin of the Short-lived Cocoon in 3C 84: Powered by Tidal Disruption Events? - Nozomu Kawakatu; Motoki Kino; Keiichi Wada (The Astrophysical Journal)
We evaluated the jet power and the density of ambient matter in 3C 84 by using the momentum balance along the jet axis and the transonic condition for the cocoons observed at two different scales (approximately 1 and 6 pc). For the inner cocoon, we precisely determined the ratio of jet power to ambient density L _j / n _a to be (0.3–0.7) × 10 ^43 erg s ^−1 cm ^3 . Similarly, for the outer cocoon, we found that this value is more than an order of magnitude larger at (0.9–3.7) × 10 ^44 erg s ^−1 cm ^3 . This indicates that the outer cocoon is formed by a powerful jet that propagates through an ambient density of 20–300 cm ^−3 with a jet power of 10 ^45−46.5 erg s ^−1 . On the other hand, the inner cocoon is formed by a weaker jet with a power of 10 ^43−44 erg s ^−1 , propagating through a relatively low-density environment of 6–20 cm ^−3 . These results suggest that (1) with respect to the difference in n _a , it appears to support the hypothesis that the inner cocoon, recently formed about 10 yr ago, is expanding in the low-density environment created by the jet emitted about 25–50 yr ago; (2) to achieve the short-lived and high L _j that generated the outer cocoon, a large mass-accretion rate is required over a short period to activate the jet. These may imply an extreme accretion event driven by the tidal disruption events of massive stars and/or the disk instability.